1 - Gabriella, Tiffani; Revia Sandy Fista, Brigitta; Yuli Purnama, Finsensius (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
This study focuses on how conversational interactivity among netizens on the social media platform X (Twitter) unfolds in relation to the childfree issue. This topic is noteworthy because, in Indonesia, prevailing social values still regard the choice to remain childless after marriage as unusual. In this research, “interactivity” refers to the ways in which interactions occur in the digital public sphere, thereby shaping meanings toward a topic—in this case, the childfree discourse. The study employs a qualitative, interpretative approach using the social media netnography method developed by Robert Kozinets in 2020. The findings indicate that the sentiments expressed tend to be negative, marked by verbal abuse directed at Gita Savitri and other users holding different views. The analysis also reveals the role of actors within the communication network, visualized using the Gephi application. The conversations are underpinned not only by patriarchal ideology but also by misogyny and modernization. On the other hand, modernization has shifted societal views on women’s roles, as well as on the notions of womanhood and motherhood.